Export logistics infrastructure and export competitiveness in the East African Community - Anthony Moni Olyanga; Isaac M. B. Shinyekwa; Muhammed Ngoma; Isaac Nkote Nabeta; Timothy Esemu; Moses Kamya (Modern Supply Chain Research and Applications, 2022)
Purpose - The purpose of this paper is to examine the influence of export logistics components: shipment arrangements, timely delivery, customs quality, trade infrastructure, and tracking and tracing on export competitiveness of firms in the East African Community (EAC). Design/methodology/approach - The study adopted the Structural Gravity Model and the Poisson pseudo- maximum likelihood (PPML). PPML a nonlinear estimation method was applied in STATA on a balanced panel data for the period of 2007-2018. Data were obtained from World Bank International Trade Centre (ITC), World Bank Logistics Performance Index (LPI) and World Bank development indicators. Findings - Results show that timely delivery and tracking and tracing of exports are positive and significant predictors of export competitiveness in EAC countries. Conversely, shipment arrangements, customs quality and trade infrastructure have no influence on export competitiveness. Research limitations/implications - The results of this study show that export logistics components of shipment arrangements, customs quality and trade infrastructure do not matter at the present in improving export competitiveness in the EAC. There is a need to examine the intricate nature of the EAC economy to further this study's findings. Practical implications - The EAC partner states should embrace deep integration by removing the behind the border trade barriers in addition to other trade restrictions, to create a common economic space among member states. This will further shrink the delivery time and the tracking and tracing of exports hence improving the competitiveness of EAC exports within the region and outside. Also, common and harmonized trade policies and regulations should be implemented through mutual recognition agreements where countries agree to recognize one another's conformity assessments. Originality/value - This study explains the complex dynamic interactions of export logistics factors in the EAC using quantitative data and that this interaction has an effect on the export competitiveness in import- dominated countries with less harmonization in their trade policies.
Keywords: 650; Customs quality; EAC; Export competitiveness; Export logistics infrastructure; Shipment arrangements; Timely delivery; Tracking and tracing; Trade infrastructure